PENGARUH KEIKUTSERTAAN DALAM PENYULUHAN TENTANG IMUNISASI TERHADAP TINGKAT PENGETAHUAN MASYARAKAT - Riri Safitri; Reni Aprinawaty Sirait; Novita Br Ginting Munthe (JURNAL KESMAS DAN GIZI (JKG), 2021)
Although many parents have brought their children to health workers to get immunizations, only a small proportion of parents have knowledge of immunization. So that sometimes there is fear and anxiety after the child is immunized. This is due to the lack of knowledge from parents about immunization. From the background that has been described above, the researchers are interested in examining whether there is an effect of extension on the level of public knowledge in Desa Pasar VI Kualanamu about immunization. The method used in this study is a comparative study with a cross sectional approach. The research sample was taken by accidental sampling technique with a total of 60 respondents. This research was conducted in October 2020 in Pasar VI Kualanamu Village, Beringin District. Data collection was carried out according to health protocols. The instrument used was a questionnaire on respondent characteristics, a questionnaire about immunization knowledge. The data analysis technique used in this study was the Mann-Whitney Test. The results of this study indicate that extension activities are an effective means of conveying information to the public. The level of knowledge of respondents about immunization in the group of extension participants was dominated by respondents who had high scores. Meanwhile, the non-counseling participants were dominated by respondents who had low scores. Based on the results of the analysis using the Mann-Whitney Test to see the effect of counseling on the level of community knowledge in Desa Pasar VI Kualanamu about immunization, it was found that there was a difference in the level of knowledge of respondents about immunization between groups of extension participants and non-participants.